2022
DOI: 10.1080/21655979.2022.2075306
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA TUG1 alleviates diabetic retinal vascular dysfunction through regulating miR-524-5p/FGFR2

Abstract: Long noncoding RNAs (LncRNAs) have been shown to play critical roles in the development of diabetic retinopathy (DR), which is often regarded as the most frequent cause of visual loss in the world. This study investigated the effect and mechanism of lncRNA taurine-upregulated gene 1 (TUG1) in DR. Quantitative real-time polymerase chain reaction (qRT-PCR) revealed that TUG1 was upregulated in streptozotocin (STZ)-induced rat model of DR and human retinal microvascular endothelial cells (hRMECs) incubated with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The blood glucose of the blood from tail vein of rats was monitored. When the random blood glucose was higher than 16.7 mmol/L and maintained for more than 1 week, the rat DR model was considered to be successful [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The blood glucose of the blood from tail vein of rats was monitored. When the random blood glucose was higher than 16.7 mmol/L and maintained for more than 1 week, the rat DR model was considered to be successful [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…AMPK senses and responds to energy deficits, while SIRT1, a deacetylase, modulates various cellular processes, including metabolism, stress response, and longevity ( Gan et al, 2018 , Tang et al, 2023 ). Both AMPK and SIRT1 play pivotal roles in conditions like diabetes, obesity, and age-related disorders, positioning them as potential targets for therapeutic interventions ( Tian et al, 2022 ). Wei et al focused on the increasing rate of obesity and T2DM, particularly among younger individuals, and the effectiveness of sleeve gastrectomy (SG) as a treatment.…”
Section: Tug1 and Diabetesmentioning
confidence: 99%
“…FGFR2 was identified as a target of miR-524-5p, with elevated expression in high glucose-treated cells. Suppressing TUG1 improved retinal vascular function in diabetes-induced impairment, indicating a potential therapeutic avenue for DR ( Tian et al, 2022 ). Anti-VEGF therapy is a treatment approach that focuses on VEGF, a protein that promotes blood vessel development ( Porta and Striglia, 2020 ).…”
Section: Role Of Tug1 In Diabetes-associated Diseasesmentioning
confidence: 99%
“…Particularly, in diabetic patients with DR or in human retinal endothelial cells cultured with HG concentrations, the upregulation of several different lncRNAs has been recently reported. Although further analyses are needed, for most of the mentioned lncRNAs, preliminary evidence suggests a putative role in DR. Of note, the in vitro knockdown of these lncRNAs ameliorates retinal dysfunctions improving various related-biological processes, such as proliferation, apoptosis, migration, angiogenesis, inflammation, or redox state [ 62 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ]. For instance, ARPE-19 cells exposed to HG display increased expression of IGF2 Antisense RNA ( IGF2-AS ) and enhanced apoptosis, and IGF2-AS silencing restrains apoptosis, inducing IGF2/Akt signaling and reducing Casp-9 expression [ 114 ].…”
Section: Long Non Coding Rnas With Increased Expression In Diabetic R...mentioning
confidence: 99%
“…Moreover, the Long Intergenic Non-Coding RNA 963 ( LINC00963 ) may regulate the proliferation and apoptosis in HG-induced HERCs by directly targeting miR-27b [ 123 ]. Additionally, a recent work reports that the knockdown of TUG1 ameliorates diabetic retinal vascular dysfunction through regulating miR-524-5p/ FGFR2 axis [ 124 ]. Furthermore, independent studies in patients with DR showed the negative correlations between Plasmacytoma Variant translocation 1 ( PVT1 ) and miR-128-3p, as well as between the lncRNA OGRU and miR-320, supporting that also these lncRNAs may affect miRNA-mediated networks [ 62 , 125 ].…”
Section: Long Non Coding Rnas With Increased Expression In Diabetic R...mentioning
confidence: 99%